Pre- and postpartum metabolizable protein supply: I. Effects on feed intake, lactation performance, and metabolic markers in transition dairy cows - T.A. Westhoff; T.R. Overton; J.N. Tikofsky; M.E. Van Amburgh; C.M. Ryan; S. Mann (Journal of Dairy Science)
ABSTRACT: The objective of this study was to investigate the effect of increasing MP supply in the prepartum, postpartum, or both diets on intake, performance, and metabolic indicators. Multiparous Holstein cows (n = 96) were assigned to 1 of 4 treatment groups at 28 d before expected calving following a randomized block design. Prepartum diets were formulated to contain either a control (CON; 85 g of MP/kg DM) or high (HI; 113 g of MP/kg DM) level of estimated MP. From calving to 21 DIM, diets were formulated to contain either a CON (104 g of MP/kg DM) or HI (131 g of MP/kg DM) level of estimated MP. To control the potential confounding effect of Met and Lys supply, diets were formulated to supply an equal amount at 1.24 and 3.84 g/Mcal of ME in both prepartum diets and 1.15 and 3.16 g/Mcal of ME in both postpartum diets, respectively. The combination of a pre- and postpartum diet resulted in 4 treatment groups: (1) CON-CON (CC; n = 23), (2) CON-HI (CH; n = 24), (3) HI-CON (HC; n = 22), and (4) HI-HI (HH; n = 23). A common lactation diet (113 g of MP/kg DM) was fed from 22 DIM to the end of the observation period at 42 DIM. Milk yield and DMI were collected daily, and plasma metabolic indicators (BHB, fatty acids [NEFA], PUN, and glucose) were determined twice weekly from −28 to 28 d relative to calving and once weekly from 29 to 42 DIM. Samples with BHB ≥1.2 mmol/L between 3 and 10 DIM were considered hyperketonemia events. Milk composition was determined weekly. Milk yield during 1 to 21 DIM was greater in HH (44.7 ± 1.0 kg/d) compared with CC (39.2 ± 1.0 kg/d) and HC (38.0 ± 1.0 kg/d) and milk yield in CH (42.4 ± 0.9 kg/d) was greater than HC, respectively. From 22 to 42 DIM, milk yield was greater in CH (53.3 ± 1.0 kg/d) and HH (54.1 ± 1.0 kg/d) compared with CC (49.6 ± 1.0 kg/d) and HC (49.3 ± 1.0 kg/d). Dry matter intake (% of BW) and concentrations of milk protein, fat, and total solids were not affected by treatment. Prepartum concentrations of PUN were greater in HI compared with CON. From 1 to 21 DIM, PUN concentrations were greater in CH and HH compared with CC and HC. From 1 to 21 DIM, concentrations of glucose were lower in HH compared with HC, and BHB were greater in CH and HH compared with HC. Concentrations of NEFA, as well as the number of hyperketonemia events did not differ by treatment during this time. From 22 to 42 DIM, concentrations of NEFA were greater in HH compared with HC and concentrations of BHB were greater in CH and HH compared with HC. Overall, feeding CH or HH increased lactation performance without altering intake or hyperketonemia events. Results from this study support formulating a fresh diet to reduce the negative MP balance during early lactation.